8.0k views
1 vote
If 2x^2+5x-12 = (2x-3)(x+4), which equation(s) should be solved to find the roots of 2x^2+5x-12=0? Check all that apply.

User Mibollma
by
4.6k points

2 Answers

6 votes

Explanation:

Question 2 of 10 If 2x ^ 2 + 5x - 12 = (2x - 3)(x + 4) which equation(s) should be solved to find the roots of 2x ^ 2 + 5x - 12 = 0 Check all that apply.

User Thebreiflabb
by
5.2k points
7 votes

ANSWER

2x-3=0

and

x+4=0

EXPLANATION

Given that:


2 {x}^(2) + 5x - 12 = (2x - 3)(x + 4)

Then to find roots of


2 {x}^(2) + 5x - 12 = 0

is the same as finding the roots of


(2x - 3)(x + 4) = 0

By the zero product property, we must have either,


2x - 3 = 0 \: or \: x + 4 = 0

Hence the equations that must be solved to find the roots are:

2x-3=0

and

x+4=0

User Asicfr
by
5.0k points